Kendala Pengembangan Investasi Kelapa Sawit dalam Perspektif Hukum - Ikarini Dani Widiyanti; Pratiwi Puspitho Andini; Emi Zulaika (Fakultas Hukum Universitas Islam Jember, 2018)
True law aims to create legal certainty, justice and expediency. Palm oil management in Indonesia certainly cannot be separated from the legal aspects, mainly related to the legal substance or regulation. The regulation of palm oil management in Indonesia is contained in various laws and / or policies, both those which regulate explicitly and implicitly. In fact, these arrangements have not fully been able to realize legal objectives, primarily legal certainty. This statement is indicated by the existence of several arrangements that are still inconsistent between one law and another. There are several factors that are constraints to the development of investment in the field of oil palm in the legal perspective, namely the inconsistency of the rules between the Act, the Presidential Regulation and the Ministerial Regulation and the number of Regional Regulations (Perda) that are contrary to the central Regulations which results in the difficult realization of a conducive business climate. The proposed suggestion is to inventory, identify and harmonize all relevant regulations in the field of investment and support the enactment of the Palm oil Draft. Key Words : Palm Oil Investment, Harmonisation Regulation, Legal Certainty